Development of white LED illuminants for colorimetry and recommendation of white LED reference spectrum for photometry. (28th June 2018) - Kokka, Alexander; Poikonen, Tuomas; Blattner, Peter; Jost, Sophie; Ferrero, Alejandro; Pulli, Tomi; Ngo, Mathias; Thorseth, Anders; Gerloff, Thorsten; Dekker, Paul; Stuker, Florian; Klej, Adam; et al.
Abstract: General lighting is undergoing a revolutionary change towards LED-based technologies. To provide firm scientific basis for the related colorimetric and photometric measurements, this paper presents the development of new white-LED-based illuminants for colorimetry, and their evaluation to recommend a new reference spectrum for calibration of photometers. Spectra of 1516 LED products were measured and used to calculate eight representative spectral power distributions for LED sources of different correlated colour temperature categories. The suitability of the calculated representative spectra for photometer calibration was studied by comparing average spectral mismatch errors with CIE Standard Illuminant A, which has been used for decades as the reference spectrum for incandescent standard lamps in calibration of photometers. It was found that in general, when compared with Standard Illuminant A, all the potential LED calibration spectra reduced spectral mismatch errors when measuring LED products. Out of the potential LED calibration spectra tested, the white LED spectrum with correlated colour temperature of 4103 K was found to be the most suitable candidate to complement Standard Illuminant A in luminous responsivity calibrations of photometers. When compared with Standard Illuminant A, employing the 4103 K reference spectrum reduced the spectral mismatch errors, on average, by approximately a factor of two in measurements of LED products and lighting. Furthermore, the new LED reference spectrum was found to reduce the spectral mismatch errors in measurements of daylight, and many types of fluorescent and discharge lamps, indicating that the proposed reference spectrum is a viable alternative to Standard Illuminant A for calibration of photometers.